Determinação multirresíduo de agrotóxicos em noz-pecã empregando método QuEChERS modificado e LC-MS/MS - Barci, Paulo Emílio Pereira (2019)
Pecan nuts is one of the few native nuts species from the American continent. The area in southern Brazil dedicated to pecan production is directly linked to the favorable climate of this region. Considering the commercialization growth of this product, there is a need to develop multiclass pesticide methods to analyze different pesticides in pecan nuts. Pecan is a commodity that contain high amount of lipids. It is a big challenge for sample preparation to quantify pesticides in low concentration. It could become interference in the analysis. The aim of this study was to establish a sample preparation method for determination of 47 pesticide residues in pecan nuts using liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). The method based on QuEChERS procedure involves acetonitrile extraction, different salts partition and clean-up with C18 and PSA. This mixture of sorbents showed significant results in number of compounds compared to other commercial sorbents. The method was validated evaluating the parameters linearity, accuracy, precision, limit of detection (LOD), limit of quantification (LOQ) and matrix effect. The determination of pesticide residues in pecan nuts samples presented to be simple, fast and effective for pesticide multiresidue determination. The validation results, evaluated by recovery assays at 5 spiked levels, were satisfactory, with accuracy from 70 to 120%, RSD ˂20%, linearity from 5 to 250 μg kg-1, determination coefficient (r2) >0.99, method LOD of 2 and 3 μg kg-1 and LOQ of 5 and 10 μg kg-1. The proposed method was applied to pecan samples obtained from different regions of Rio Grande do Sul State (Brazil); Buenos Aires (Argentina) and Santiago (Chile). No pesticide residues were detected in these samples. The proposed method proved to be efficient and robust allowing the use in routine analysis.